Real-world pharmacovigilance of risperidone: Analysis based on FAERS reports from physicians and pharmacists - Gang Hao; Zhi Jia; Yue Zan; Xiaomin Lv; Na Li; Junyin Zhou (PLoS ONE, 2025)
Objective Risperidone, a second-generation antipsychotic widely used in clinical practice, has not been systematically evaluated for its long-term real-world adverse events. This study analyzed risperidone-related AEs reported in the U.S. Food and Drug Administration Adverse Event Reporting System (FAERS) over nearly two decades, providing a reference for clinical medication. Methods Data on risperidone was collected from FAERS covering the period from the first quarter of 2004 to the third quarter of 2024. Signal detection was performed using the reporting odds ratio, proportional reporting ratio, Bayesian confidence propagation neural network, and multi-item gamma Poisson shrinker algorithms. Results Among the 18,089 reports collected, a total of 27 system organ classes and 452 preferred terms were identified. Nervous system disorders, Psychiatric disorders, General disorders and administration site conditions, and Injury, poisoning and procedural complications were the primary SOCs. Additionally, Reproductive system and breast disorders, Endocrine disorders, Metabolism and nutrition disorders, and Cardiac disorders showed a strong association with risperidone, warranting heightened vigilance. This study identified a substantial number of extrapyramidal-related AEs, including propulsive gait, spasmodic dysphonia, tongue thrust, respiratory dyskinesia, oromandibular dystonia, cogwheel rigidity, and pleurothotonus. Rare cardiovascular events such as Wellens’ syndrome and endocarditis fibroplastica were also uncovered through in-depth analysis. Furthermore, AEs like paroxysmal perceptual alteration, pulmonary vein occlusion, and floppy iris syndrome, although infrequent, exhibited high signal strength. This study also identified noteworthy signals not included in the risperidone label, such as rabbit syndrome (perioral tremor), jaw clicking, and portal vein cavernous transformation, which merit further investigation. Conclusion From the perspectives of physicians and pharmacists, this research provides a unique and robust theoretical foundation for evaluating the safety profile of risperidone and offers direction for future studies on its adverse events.